IOLE cooperative learning model in improving students’ collaborative character and reading literacy - Farisa Mardiani; R. Rusdarti; Panca Dewi Purwati (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The character of cooperation and literacy of students today still needs to improve. Effective learning model modifications are required to enhance students' collaborative character and literacy. The purpose of the research is to analyze the effectiveness of the IOLE (inside outside learning) learning model on the character of student collaboration and literacy. The research design used quasi-experimental methods with the control group. For each intervention and control group, research samples of as many as 12 elementary students in grade V. The research was carried out in November 2023 at two elementary schools in the Kudus District. Research instruments use pretests and posttests on the history of cigarettes to evaluate reading literacy. The observation sheet is used to assess the character of cooperation. The study's results showed an influence of the IOLE learning model on collaborative character (p=0,002) and reading literacy (p =0,002) in elementary students. This model can be implemented in primary schools, especially by the teacher of the fifth grade, as a form of learning innovation that can be done to the learning objectives, in particular, the character of cooperation and student reading literacy. AbstrakKarakter kerjasama dan literasi membaca siswa saat ini masih tergolong rendah. Perlu adanya modifikasi model pembelajaran yang efektif untuk meningkatkan karakter kerja sama dan literasi membaca siswa. Tujuan penelitian untuk menganalisis keefektifan model pembelajaran IOLE (inside outside learning) terhadap karakter kerja sama dan literasi membaca siswa. Desain penelitian menggunakan quasi experimental with control group. Sampel penelitian sebanyak 12 siswa SD kelas V untuk masing-masing kelompok intervensi dan kontrol. Penelitian dilakukan pada Bulan November 2023 di 2 SD Negeri di Kabupaten Kudus. Instrumen penelitian menggunakan pretest dan posttest mengenai sejarah rokok kretek untuk menilai literasi membaca. Lembar observasi digunakan untuk menilai karakter kerja sama. Hasil penelitian menunjukkan terdapat pengaruh model pembelajaran IOLE terhadap karakter kerja sama (p=0,002) dan literasi membaca (p=0,002) pada siswa SD. Model pembelajaran IOLE efektif meningkatkan karakter kerja sama dan literasi membaca siswa SD sehingga mendukung capaian tujuan pembelajaran siswa khususnya pada mata pelajaran bahasa Indonesia. Model ini dapat diimplementasikan di sekolah dasar khususnya oleh guru kelas V sebagai bentuk inovasi pembelajaran yang dapat dilakukan untuk mencapai tujuan pembelajaran khususnya karakter kerja sama dan literasi membaca siswa.Kata Kunci: karakter kerjasama; literasi membaca; model pembelajaran IOLE